Long-term Breastfeeding in the Prevention of Allergic Rhinitis: Allergic Rhinitis Cohort Study for Kids (ARCO-Kids Study) - Han, Doo Hee; Shin, Jae-Min; An, Seokyung; Kim, Jong Seung; Kim, Dong-Young; Moon, Sungji; Kim, Jung-Soo; Cho, Joong Saeng; Kim, Si Whan; Kim, Young Hyo; Roh, Hwan-Jung; Shim, Woo Sub; et al. (Clinical and experimental otorhinolaryngology, 2019)
There is a great deal of interest in the possibility that environmental factors may influence the risk of developing allergic rhinitis (AR) in early life. We investigated the simultaneous effects of mode of delivery and duration of breastfeeding on the development of AR in children. Data from 1,374 children participating in the Allergic Rhinitis Cohort Study for kids (ARCO-kids study) was analyzed. All subjects were divided into AR or non-allergic rhinitis (NAR) groups. Data on environmental factors, mode of delivery and duration of breastfeeding were collected using a questionnaire. Compared with short-term breastfeeding (<6 months), long-term breastfeeding (≥12 months) was significantly associated with a lower prevalence of AR (adjusted odds ratio [aOR], 0.54; 95% confidence interval [CI], 0.34 to 0.88). Children in the AR group also had a higher cesarean delivery rate than those in the NAR group (39.1% vs. 32.8%, P=0.05). Regarding the combined effects of mode of delivery and duration of breastfeeding, long-term breastfeeding with a vaginal delivery strongly suppressed the development of AR, compared to short-term breastfeeding with a cesarean delivery (aOR, 0.47; 95% CI, 0.30 to 0.73). Long-term breastfeeding (≥12 months) and a vaginal delivery are associated with a lower risk of developing childhood AR.